Conducting research literature reviews : from the internet to paper - Fink, Arlene (Thousand Oaks, California : SAGE, 2014)
"In Conducting Research Literature Reviews, author Arlene Fink providing readers with an accessible, in-depth look at how to synthesize research literature. She shows readers how to explain the need for and significance of research, as well as how to explain a study's findings. Offering a step-by-step approach to conducting literature reviews, this edition has been completely updated to address the online nature of most literature searches."--[book cover].
Reviewing the literature: Why? For whom? How? -- Searching and screening: the practical screen and methodological quality (Part 1-Research design and sampling) -- Searching and screening: methodological quality (Part 2-Data collection, interventions, analysis, results, and conclusions) -- Doing the review: a reader's guide chapter -- What did you find? Synthesizing results.
Includes bibliographical references and index.
Keywords: Research -- Methodology; Research -- Evaluation; Bibliography -- Methodology